Balzac and the African Explorer: Cognitive Mapping of the faubourg Saint-Germain - Yee, J (University of Nebraska Press, 2017)
A fresh reading of Balzac’s La Duchesse de Langeais (1834) reveals that the geography of African exploration, and of Andalusia as a liminal space between Europe and Africa, are mapped onto the geography of Paris. The class boundaries that separate the aristocratic faubourg Saint-Germain from the rest of Paris make its conquest, in the synecdochic form of the Duchess’s heart, as problematic as the exploration of central Africa from which the protagonist Montriveau has just returned. A spatial reading of this kind reveals the profound unity of Balzac’s novella despite its three-part, a-chronological structure. This article argues for the crucial importance of travel writing in understanding this novella, which can be seen as a form of secondary travel writing. More specifically, it is argued that Balzac is responding directly to a travel narrative by René Caillié that was published in 1830. As a result new light can be shed on La Duchesse de Langeais by critical approaches to narratives of travel and exploration, notably Mary Louise Pratt’s notions of the “contact zone” and the “anti-conquest” narrative. The latter is invaluable in understanding the figure of Montriveau, whose voyage is one of pathos, suffering and epistemological failure (he does not bring back the information that he sought), aspects that draw on Caillié’s real-life experience. The novella can, more broadly, be read in the light of Fredric Jameson’s concept of “cognitive mapping”, with its suggestion of a cognitive or epistemological failure at the heart of the European project to reach a fully global world-view. Balzac’s Comédie humaine, despite its vast geographical, social and historical mapping of the French system, is already shot through with awareness of the failure or incompletion of a mapping project that would extend to a global vision.